O Level islamiyat paper 1 (2058/1) skills book - Sohrwardy, khalid hameed (Cambridge University Press; Karachi, 2014)
O Level Islamiyat Paper 1 (2058/1) Skills Book by Khalid Hameed offers a structured guide to mastering key skills and concepts required for success in the Islamiyat exam, with practice questions and solutions.